Prevalence and spread of enterohepatic Helicobacter species in mice reared in a specific-pathogen-free animal facility - Bohr, U. R.M.; Selgrad, M.; Ochmann, C.; Backert, Steffen; König, Wolfgang; Fenske, A.; Wex, T.; Malfertheiner, P. (Journal of Clinical Microbiology, 2006)
Infections with enterohepatic Helicobacter species (EHS) can change the results of animal experiments. However, there is little information about the prevalence of EHS in noncommercial animal facilities. The aim of this study was to investigate the prevalence and the spread of EHS in specific-pathogen-free (SPF) mice. Fecal samples of 40 mouse lines were analyzed for members of the family Helicobacteraceae using a group-specific PCR targeting the 16S rRNA gene. Additional experiments were carried out to evaluate the spread of EHS among mice harbored in different caging systems. Helicobacter species were detected in 87.5% of the mouse lines tested. Five different Helicobacter species were identified: H. ganmani, H. hepaticus, H. typhlonicus, and the putative Helicobacter species represented by the isolates hamster B and MIT 98-5357. Helicobacter infection did not spread between animals in neighboring cages when individually ventilated cages were used; in contrast, when the mice were reared in open-air cages, EHS were found to spread from cage to cage. However, the spread was prevented by adding polycarbonate filter tops to the cages. When Helicobacter-negative and infected mice shared the same cage, transmission of the infection occurred in 100% within 2 weeks. Furthermore, we found that mice from commercial breeding facilities may carry undetected Helicobacter infections. Taken together, we show that infection with EHS may frequently occur and spread easily in mice reared under SPF conditions despite extensive safety precautions. Moreover, there is a high prevalence of rather uncommon Helicobacter species that may be a consequence of the current routine procedures used for health screening of SPF mice. Copyright © 2006, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up